"Reproducing the social": contradictory interconnections between land, cattle production and household relations in the Besters Land Reform Project, South Africa. Issue 3 (1st October 2019) - Hornby, Donna; Cousins, Ben
Abstract : Land redistribution policy in South Africa emphasises commercial farming as the legitimate use of land. This production-oriented framework fails to take into account the intertwined but unstable relationship between the production of market value and social reproduction, and how this shapes social differentiation. Drawing on a case study of the Besters Land Reform Project in the province of KwaZulu-Natal, the paper shows that land and cattle are not simply moments in the production of beef but material and discursive resources in (re)making the social conditions of the household. Cattle are used in drawn-out ceremonies that occur in specific spaces and stitch together families and communities pulled apart by rising inequality, making land constitutive of identity and belonging as well as of capitalist value production. Until land reform policy recognises the multi-functionality of land and cattle, and the contradictory relationship between functions, agricultural production will be a limited indicator of "success" or "failure."